COMPARISON OF MSME POLICY LEGAL IN VARIOUS COUNTRIES: PERBANDINGAN HUKUM KEBIJAKAN UMKM DI BERBAGAI NEGARA - Hakim, Lukmanul (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2025)
Micro, Small and Medium Enterprises or commonly known as MSMEs have an important role in the current global economy, especially in Indonesia. However, the regulations and policies governing this sector in each country are different, depending on the legal system and economic policies implemented in that country. This study aims to analyze and compare legal policies related to MSMEs in several countries, including Indonesia, the United States, Japan and Germany. By using normative and comparative research methods, the results of this research reveal the various approaches taken by these countries in supporting MSMEs, both in terms of regulations, tax incentives, access to capital and legal protection. The policies taken by each country are policies that encourage the growth and development of MSMEs in that country where there are several similarities and differences related to existing regulations in Indonesia itself, for this reason there needs to be a common perception between institutions that have programs development of MSMEs to synergize to support existing policies as a form of implementation.